Maus II : a survivor's tale : and here my troubles began - Spiegelman, Art. (New York : Pantheon Books, 1991)
A continuation of the story begun in the Pulitzer Prize winning "Maus," in which the author relates, in cartoon form, his father's experiences as an inmate at Auschwitz during World War II. Illustrations portray Jews as mice and Nazis as cats.
"Chapters one through four were originally published in somewhat different form in Raw magazine between 1986 and 1991"--T.p. verso.
Sequel to: Maus: A Survivor's Tale; My Father Bleeds History.
Library Journal Starred
Wilson's Junior High School
Wilson's Senior High School
Book Report, April 2010
Keywords: Spiegelman, Art -- Comic books, strips, etc; Spiegelman, Vladek -- Comic books, strips, etc; Spiegelman, Art -- Comic books, strips, etc; Spiegelman, Vladek -- Comic books, strips, etc; Children of Holocaust survivors -- United States -- Biography -- Comic books, strips, etc; Holocaust survivors -- United States -- Biography -- Comic books, strips, etc; Holocaust, Jewish (1939-1945) -- Poland -- Biography -- Comic books, strips, etc; Comic books, strips, etc; Holocaust survivors -- Biography; Holocaust, 1939-1945 -- Biography